2017
DOI: 10.1371/journal.pone.0173362
|View full text |Cite
|
Sign up to set email alerts
|

Systemic thioridazine in combination with dicloxacillin against early aortic graft infections caused by Staphylococcus aureus in a porcine model: In vivo results do not reproduce the in vitro synergistic activity

Abstract: IntroductionConservative treatment solutions against aortic prosthetic vascular graft infection (APVGI) for inoperable patients are limited. The combination of antibiotics with antibacterial helper compounds, such as the neuroleptic drug thioridazine (TDZ), should be explored.AimTo investigate the efficacy of conservative systemic treatment with dicloxacillin (DCX) in combination with TDZ (DCX+TDZ), compared to DCX alone, against early APVGI caused by methicillin-sensitive Staphylococcus aureus (MSSA) in a por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Toleration of the clinical relevant concentrations of the helper-drugs by the animals (or humans) is probably underrated [13] e.g. in another recent published study evaluating in vivo helper-compound activity of thioridazine, also a neurotrophic active medical compound, the authors report that their study had to pre-terminate due to severe side-effects of thioridazine in pigs with the concentrations used [22].…”
Section: Discussionmentioning
confidence: 99%
“…Toleration of the clinical relevant concentrations of the helper-drugs by the animals (or humans) is probably underrated [13] e.g. in another recent published study evaluating in vivo helper-compound activity of thioridazine, also a neurotrophic active medical compound, the authors report that their study had to pre-terminate due to severe side-effects of thioridazine in pigs with the concentrations used [22].…”
Section: Discussionmentioning
confidence: 99%
“…Активностью Продемонстрировано, что дериват фенотиазина -антипсихотический препарат тиоридазин (thioridazine) подавляет транскрипцию нескольких генов, принадлежащих регулону VraRS и участвующих в биосинтезе аминокислот, транспортеров, компонентов стенки бактерий Staphylococcus aureus [7,40]. Применение тиоридазина повышает восприимчивость бактерий MRSA к действию β-лактамных антибиотиков [34,38,39]. Mette Thorsing и соавт.…”
Section: лекарственные средства ингибирующие гистидинкиназыunclassified
“…The concentration of phenothiazines must be relatively high to obtain the synergistic effects, and studies have revealed that these compounds did not perform well as helper compounds when tested in vivo . In some cases, the administrated dose needed to be reduced considerably due to severe side-effects observed in the phenothiazine-treated animals ( Stenger et al, 2015 , 2017 ). Since phenothiazines possess lipophilic properties, they can easily cross the blood-brain barrier (BBB) and cause effects on the central nervous systems (CNS) ( Seelig et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%